Dukungan Sosial Dosen terhadap Hardiness pada Mahasiswa Tingkat Akhir - Asrina Endarwaty; Hapsa Sangkota (Jurnal Ragam Pengabdian, 2026)
Hardiness is a much needed skill for final year students. With hardiness, students are able to persevere and manage stress in facing their academic problems. However, increasing hardiness cannot be separated from the social support of lecturers. This study employs a qualitative approach using phenomenological methods to explore participants' experiences in depth, particularly regarding the challenges they face as final-year students, the forms of social support they receive from lecturers, and the relationship between these factors and their hardiness in completing their final assignments. The study participants include final-year students who are currently writing their theses and were selected using purposive sampling techniques. Data collection was conducted through in-depth interviews and supporting documentation. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results of the study showed that final-year students face various challenges, both academic and psychological. The social support received by students from lecturers took the form of emotional, informational, evaluative, and instrumental support. This support played a role in strengthening students' hardiness, namely by increasing their self-confidence, involvement and commitment, and helping them to interpret pressure as a challenge.